HAVACILIK ÇALIŞANLARININ YAŞAM DOYUMUNUN DEMOGRAFİK DEĞİŞKENLER AÇISINDAN DEĞERLENDİRİLMESİ - Engin Kanbur; Alper Erol (Sosyal Ekonomik Arastirmalar Dergisi, 2017)
ABSTRACT

Aviation sector is constantly evolving and changing with the effects of technology and globalization. This evolution and change brings with it many positive and negative events which can affect life satisfaction of employees. It is thought that some negative situations such as increased workload, complex business processes that new technologies can bring, flight intensity, fatigue, stress, burnout can affect life satisfaction of employees. Life satisfaction is defined both as positive or negative situations which an individual has encountered in work life and as positive and negative situations which he has encountered in social life external to work life, and it affects life pleasure of individual as a whole. The life satisfaction, which is also defined as the situation attained with comparison of expects of the individual and what he/she already has, is the sum of the positive or negative events lived by the individual during his/her work and social life. The aim of the study is to examine the aviation employees' life satisfaction due to their demographic characteristics. Data of the research were collected by questionnaire from 263 employees of a company in aviation sector. First part of the questionnaire contains demographic questions and second part of the questionnaire contains questions related with life satisfaction of employees. The reliability of life satisfaction scale used in the study was determined as 86,3%. How aviation employees’ life satisfaction differ due to their demographic characteristics is examined by using variance and t-test analysis. According to research findings; life satisfaction of aviation employees was found significantly different due to their education, age and total seniority but there wasn't seen any differences due to their marital status and hobbies

Keywords: Life Satisfaction, Aviation, Human Factors, Demographic Characteristics

JEL Codes: M10, M19
Keywords: demografik özellikler; HF5001-6182; yaşam doyumu; demographic characteristics; aviation; i̇nsan faktörleri; Business; havacılık; life satisfaction; human factors; 8. Economic growth